2012
DOI: 10.1021/ml300192k
|View full text |Cite
|
Sign up to set email alerts
|

Structure–Activity Relationships for Side Chain Oxysterol Agonists of the Hedgehog Signaling Pathway

Abstract: Oxysterols (OHCs) are byproducts of cholesterol oxidation that are known to activate the Hedeghog (Hh) signaling pathway. While OHCs that incorporate hydroxyl groups throughout the scaffold are known, those that act as agonists of Hh signaling primarily contain a single hydroxyl on the alkyl side chain. We sought to further explore how side chain hydroxylation patterns affect oxysterol-mediated Hh activation, by performing a structure−activity relationship study on a series of synthetic OHCs. The most active a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(32 citation statements)
references
References 25 publications
3
29
0
Order By: Relevance
“…However, the high concentration (>1 mM) of oxysterols required to activate Hedgehog signaling as well as their hydrophobic nature, which could lead to off-target effects due to their incorporation into lipid bilayers, raised concerns about the specificity of these effects. Moreover, the synthetic molecule 23(S)-OHC has a similar potency to that of 20(S)-OHC but greater selectivity toward the Hedgehog pathway compared to liver X receptor (Box 1) 69 , suggesting that the effects on other cellular pathways cannot be ruled out when interpreting oxysterol experiments. The 20(R)-OHC diastereomer of 20-OHC does not affect SMO activity in cell lines 67 , demonstrating stereospecificity.…”
Section: Allosteric Regulation Of Smo By Small Moleculesmentioning
confidence: 99%
“…However, the high concentration (>1 mM) of oxysterols required to activate Hedgehog signaling as well as their hydrophobic nature, which could lead to off-target effects due to their incorporation into lipid bilayers, raised concerns about the specificity of these effects. Moreover, the synthetic molecule 23(S)-OHC has a similar potency to that of 20(S)-OHC but greater selectivity toward the Hedgehog pathway compared to liver X receptor (Box 1) 69 , suggesting that the effects on other cellular pathways cannot be ruled out when interpreting oxysterol experiments. The 20(R)-OHC diastereomer of 20-OHC does not affect SMO activity in cell lines 67 , demonstrating stereospecificity.…”
Section: Allosteric Regulation Of Smo By Small Moleculesmentioning
confidence: 99%
“…[11] The mosta ctive compound to emerge from our study, 23(S)-OHC (4), was found to possess potency similart ot hat of 20(S)-OHC (EC 50 :0 .57 and 0.52 mm,r espectively). [11] The mosta ctive compound to emerge from our study, 23(S)-OHC (4), was found to possess potency similart ot hat of 20(S)-OHC (EC 50 :0 .57 and 0.52 mm,r espectively).…”
Section: Introductionmentioning
confidence: 65%
“…[11] The mosta ctive compound to emerge from our study, 23(S)-OHC (4), was found to possess potency similart ot hat of 20(S)-OHC (EC 50 :0 .57 and 0.52 mm,r espectively). [11] For this reason, we soughtt od evelop am ore direct and higher-yielding procedure for the synthesis of 23(S)-OHC. [13] OHC 4 was also found to induce osteogenic differentiation and osteoblast formation in cultured M2-Oxysterols (OHCs) are metabolic byproducts of cholesterol that are known to functiona sa gonists of the Hedgehog (Hh) signaling pathway.P reviously,w er eported 23(S)-hydroxycholesterol [23(S)-OHC, 4]a sapotent activator of Hh signalingw ith the ability to functionally differentiate mouse embryonic fibroblasts to an osteogenic fate.…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…The ligand-binding pocket (LBP) of LXR allows binding of side-chain oxygenated sterols (OHCs). Recently, OHCs with a specific stereochemistry at the 23-hydroxylated side-chain C atom were also shown to regulate the hedgehog signalling pathway (Hh), a key developmental pathway playing multiple roles in embryonic development, including stem cell differentiation (Corman et al, 2012). This urged us to initiate a drug-design programme, starting with a retrosynthetic analysis for the establishment of synthetic routes to the pharmacophores in the different OHCs reported to affect the various diseases referred to above.…”
Section: Commentmentioning
confidence: 99%